Institutions as determinants of preference change: one way relation? - Martin Binder; Uta-Maria Niederle (Max Planck Institute of Economics, 2006)
In recent economic literature, there has been an increasing interest in modelling preferences as endogenous. Some arguments go along the lines that institutions shape preferences. This paper suggests that adopting a more substantive concept of preferences furthers our understanding of how they systematically shape institutions. We integrate social-psychological concepts and combine them with an account of learning. Thus, a model of the dynamic interrelation between preferences and institutions can be developed. While institutional change can certainly be partly explained in terms of changing incentives, we offer an approach that goes beyond the standard explanation.
Keywords: O12; D79; Z00; 330; endogenous preferences; institutional change; learning; attitudes; wants; social instincts